A review of professionalism within LIS. Issue 2 (14th March 2017) - Cannon, Paul
Abstract : Purpose: The purpose of this paper is to examine the nature of professionalism within Library and Information Science (LIS) and in doing so draw comparisons with the education and medicine professions. Design/methodology/approach: The paper provides a review of the extant literature from the three professions and gives a brief review of the theoretical constructs of professional knowledge using the work of Eisner and Eraut to explore knowledge types. It then relates these definitions to knowledge use within LIS, education and medicine, before examining the roles that professional associations have on the knowledge development of a profession. It concludes with a reflection on the future of professionalism within LIS. Findings: The literature suggests a fragmented epistemological knowledge-base and threats to its practices from outside professions. It does, however, find opportunities to redefine its knowledge boundaries within the phronetic practices of LIS and in socio-cultural uses of knowledge. It finds strengths and weaknesses in professionalism within LIS and its practitioners. Originality/value: This review provides a contemporary update to several earlier, related, works and provides useful context to current efforts to professionalise LIS by the Chartered Institute of Library and Information Professionals.